1989
DOI: 10.1111/j.1365-2125.1989.tb05385.x
|View full text |Cite
|
Sign up to set email alerts
|

Enalapril in African patients with congestive cardiac failure.

Abstract: In a preliminary double‐blind study in African patients with heart failure, enalapril tended to increase treadmill exercise duration relative to placebo (95% confidence interval‐11.5 to 144.3 s). This was associated with a significant improvement in NYHA functional class and subjective well being (P less than 0.05 ANOVA) with a concomitant reduction in body weight (P less than 0.05 ANOVA). It significantly increased pulse pressure during forearm isometric exercise (P less than 0.05 ANOVA), but the Valsalva's m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…There have been smaller trials that confirmed the effectiveness of ACEis and b-blockers in patients from Africa and Asia. 504,509 Because of the fundamental nature of the derangements in HF, it is likely that the current treatment approach such as blockade of neurohormonal activation and the judicious use of devices will be similarly effective, although one cannot rule out the possibility that the degree of response to treatment might vary among ethnic groups. Details that pertain to specific minority populations are available in section 7.5.2.2 of the Supplementary Material.…”
Section: General Considerationsmentioning
confidence: 99%
“…There have been smaller trials that confirmed the effectiveness of ACEis and b-blockers in patients from Africa and Asia. 504,509 Because of the fundamental nature of the derangements in HF, it is likely that the current treatment approach such as blockade of neurohormonal activation and the judicious use of devices will be similarly effective, although one cannot rule out the possibility that the degree of response to treatment might vary among ethnic groups. Details that pertain to specific minority populations are available in section 7.5.2.2 of the Supplementary Material.…”
Section: General Considerationsmentioning
confidence: 99%
“…With respect to the treatment of patients with HF, relatively few large-scale randomized controlled intervention trials in HF have included regions outside Europe and the US. Smaller clinical trials (6,7) have shown the effectiveness of ACE inhibitors and betablockers in HF patients from Africa and Asia. Given the fundamental nature of the derangements in HF, our current approach, including neurohormonal blockade and the appropriate use of devices, will likely be effective, although dosages and responses may differ slightly among ethnic groups.…”
Section: General Considerationsmentioning
confidence: 99%